2000
DOI: 10.1103/physrevlett.85.46
|View full text |Cite
|
Sign up to set email alerts
|

Photoelectron Angular Distributions from OKShell of Oriented CO Molecules: A Critical Comparison between Theory and Experiment

Abstract: The dynamical information (ten dipole matrix elements and eight phase differences) has been deduced from the measured angular distributions of photoelectrons from O K shell of oriented CO molecules near the ionization threshold in the region of a sigma(*) shape resonance. Light polarization parallel and perpendicular to the molecular axis has been used. An important contribution of six lsigma partial waves with 0 Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
40
3
2

Year Published

2001
2001
2012
2012

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 38 publications
(49 citation statements)
references
References 15 publications
4
40
3
2
Order By: Relevance
“…At higher energies the RCHF approximation has also been used (CO 43,44,50,52,54,67,[115][116][117][118][119][120] , N 2 3 ). This is in contrast with the frozen core Hartree Fock (FCHF) approximation, which has widely been used in most earlier and some recent works (CO 42,48,58,74,75,106,121 , N 2 22,27,32,58,74,75,106 ).…”
Section: Theoretical Methods Within the Fixed-nuclei Approximationmentioning
confidence: 99%
“…At higher energies the RCHF approximation has also been used (CO 43,44,50,52,54,67,[115][116][117][118][119][120] , N 2 3 ). This is in contrast with the frozen core Hartree Fock (FCHF) approximation, which has widely been used in most earlier and some recent works (CO 42,48,58,74,75,106,121 , N 2 22,27,32,58,74,75,106 ).…”
Section: Theoretical Methods Within the Fixed-nuclei Approximationmentioning
confidence: 99%
“…The theoretical description of CO + states involved in the 22-40 eV energy region has been discussed previously for the interpretation of high resolution photoelectron spectrum (PES) spectra reported by Baltzer et al 26 Complementary results characterizing the CO inner-valence region have also been discussed in the experimental PES studies by Potts and Williams, 27 and Svensson et al 28 and in the calculations reported by Hayes and Nobel 29 and Ehara et al 30 Valence MFPADs have been studied for CO molecules absorbed on surfaces using circularly polarized light 31 and linearly polarized light. 32 Additionally, MFPADs in core shell ionization have been studied using circularly 33,34 or linearly 35,36 polarized light. However to our knowledge, only the PAD results of Hikosaka and Eland 37 and Eland et al 38 using the velocity imaging photoionization coincidence technique have been reported in the literature for PI of inner-valence states, in particular the 4 2 + state.…”
Section: Introductionmentioning
confidence: 99%
“…But only recently, owing to application of high intensity synchrotron radiation sources and highly sophisticated electron and ion detectors, it became possible to measure the partial photoionization cross sections and angular distributions with unprecedented overall resolution of about 0.1 eV sufficient to resolve the vibrational structure of the photoelectron spectra 2. By using an angle‐resolved photoelectron–photoion coincidence technique it became possible to select the processes corresponding to a well‐defined direction of the molecular axis in space from the photoionization of an ensemble of randomly oriented molecules 3–10. The direction of motion of the fragment ion gives the direction of the molecular axis at the moment of photoionization, provided the dissociation time is much shorter than the period of molecular rotation.…”
Section: Introductionmentioning
confidence: 99%